2019
DOI: 10.1088/1742-6596/1294/2/022003
|View full text |Cite
|
Sign up to set email alerts
|

New π-Conjugated Materials Based on Thienopyrazine As Organic Dye Sensitizers for Organic Photovoltaic Device Applications

Abstract: In this work, new organic donor-π-acceptor molecules based on thienopyrazine is designed and reported. Diverse side based electron groups were presented to evaluate their impacts on the electronic and photovoltaic properties. The calculations of ground state were done by employing the DFT-B3LYP/6-31G(d,p) and the TD-DFT method for the excitation properties of the produced molecules. The results indicated that the “HOMO” and “LUMO” level are slightly changed and this suggests that there are different structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While polythiophenes and PEDOT are commercially available organic donors, our hypothetical NMe2-PPT oligomer has not been synthesized so far. However, thieno­[3,4- b ]­pyrazine derivatives are known as components of low-band-gap polymers, and the procedures for their synthesis are described. …”
Section: Methodsmentioning
confidence: 99%
“…While polythiophenes and PEDOT are commercially available organic donors, our hypothetical NMe2-PPT oligomer has not been synthesized so far. However, thieno­[3,4- b ]­pyrazine derivatives are known as components of low-band-gap polymers, and the procedures for their synthesis are described. …”
Section: Methodsmentioning
confidence: 99%
“…The photo-electronic properties of the excited-state of dyes are essential for improving the photoelectric performance of DSSCs. In this study, The significant parameters of JSC are: the open-circuit voltage, the lowest energy absorption, the oxidation potential energy, oxidation potential energy, free energy change, dye regeneration were calculated and listed in the Table 2 using formulas from a previous study [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. It was found that the value of for all the studied dyes ranged between 0.805to 1.739eV, and it should be noted that these values are positive and good.…”
Section: Photovoltaic Propertiesmentioning
confidence: 99%
“…The DSSC is based on four parts: a nanocrystalline photoanode, a counter electrode, a redox electrolyte and dye, the dyes of which is vital in estimating the PCE of DSSC's. The dyes can be separated into metal-free, metal-bearing, and natural dyes [8,9]. Quantum chemical approaches have become an effective option of exposing the relation between dye molecules' structures and properties, providing a strong theoretical foundation for the sensitive detection of high efficiency dyes [9.10].…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that the open circuit voltage Voc is linearly dependent on the HOMO power of the donor and the LUMO of the receiver [19,21]. Table 2 shows the calculation of VOC to examine the relationship between the energy of VOC and LUMO energy of the studied dyes which depend on electron injection from the LUMO level to the conduction band of PC60BM, PC70BM or TiO2 as follows [20,21]:…”
Section: The Photovoltaic Propertiesmentioning
confidence: 99%